Comprensión de Textos - Herrera Facho, Víctor Carlos (2018)
The session entitled "We understand texts with the reading of images" was applied in students who are in the fifth grade of primary education, the analysis, understanding and reflection of images, their interest, context to encourage written production has been taken into account. The focus of the area was applied to achieve significant advances in the learning session. We worked with various active strategies and the constant participation of the students, providing feedback and formative evaluation._x000D_ The theme of the chosen text allowed to develop the oral comprehension and later the written comprehension through the development of a text, the reading comprehension competence is basic for the integral development of all the students, this must be well developed and thus be able to directly access all the curricular subjects of the education system._x000D_ A good understanding of texts will be demonstrated not only in the subject of communication but also in the other areas. In the development of the session the processes of reading before and after were used. Students were encouraged to make judgments and reflect. Also to develop a continuous practice of reading and writing, do it in a free, constant manner for the benefit of their reading and writing skills.